L'histoire des femmes au Québec depuis quatre siècles - Collectif Clio (Le Jour, 1992)
Keywords: Femmes

Les femmes et le vote au Bas-Canada, 1791-1849 - Picard, Nathalie (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Élections

Les femmes et le vote au Bas-Canada de 1792 à 1849 - Picard, Nathalie (Université de Montréal, 1992)
Keywords: Femmes; Élections

Madame James McGill (1747-1818): Marie-Charlotte Guillimin, ou, La vie d'une femme mondaine à Montréal au dix-huitième siècle - Tanguay, Lynda (Université McGill, 1993)
Keywords: Bourgeoisie; McGill, James

Women and Technological Change in Nineteenth Century Montreal - Bradbury, Bettina (Women, Work and Place, 1994)
Keywords: Femmes

The Geography of Prostitution in an Early Nineteenth-Century Urban Centre: Montreal, 1810-1842 - Poutanen, Mary Anne (Power, Place and Identity: Historical Studies of Social and Legal Regulation in Quebec, 1998)
Keywords: Femmes; Prostitution

Les procès en séparation de corps dans la région de Montréal, 1795-1879 - Cliche, Marie-Aimée (Revue d'histoire de l'Amérique française, 1995)
Keywords: Femmes; Mariage

Working Families: Age, Gender and Daily Survival in Industrializing Montreal - Bradbury, Bettina (Labour / Le travail, 1994)
Keywords: Famille; Femmes

Les maîtresses d'écoles indépendantes: une contribution essentielle à l'éducation de la jeunesse montréalaise du premier tiers du XIXe siècle - Dufour, Andrée (Les bâtisseuses de la Cité, 1993)
Keywords: Enseignants; Femmes

Le leadership féminin dans les associations privées de charité protestantes au XIXe siècle à Montréal - Harvey, Janice (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Protestants

Working Families: Age, Gender, and Daily Survival in Industrializing Montreal - Bradbury, Bettina (McClelland & Stewart, 1993)
Keywords: Famille; Femmes

"Elles ne se marièrent pas et eurent beaucoup d'enfants": analyse du discours institutionnel traitant de la mère célibataire au Québec au milieu du XXe siècle - Turcotte, Géraud (Université Laval, 1990)
Keywords: Famille; Femmes

Pigs, Cows and Boarders. Non-wage forms of Survival among Montreal Families, 1861-1881 - Bradbury, Bettina (The Challenge of Modernity: A Reader in Post-Confederation Canada, 1992)
Keywords: Famille; Femmes

Les vocations féminines de la région montréalaise au XIXe siècle - Payette, Céline (Université du Québec à Montréal, 1991)
Keywords: Communautés religieuses; Femmes

Debating Dower: Patriarchy, Capitalism and Widows' Rights in Lower Canada» - Bradbury, Bettina (Power, Place and Identity: Historical Studies of Social and Legal Regulation in Quebec, 1998)
Keywords: Femmes; Mariage; Veuvage

Class, Culture, Family and the Law: Wife to Widow in Nineteenth-Century Quebec - Bradbury, Bettina (Programme d'études sur le Québec de l'Université McGill, 1997)
Keywords: Femmes; Mariage; Veuvage

Aspects sociaux et économiques du veuvage à Montréal au milieu du 19e siècle - Favel, Valentine (Université Lumière Lyon 2, 1991)
Keywords: Famille; Femmes; Veuvage

"Against her Will and without her Consent": Women, Sexual Crimes and the Law in the District of Montreal, 1803-1843 - Ramos, Sandy (Université Concordia, 1996)
Keywords: Criminalité; Droit; Femmes

Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1994)
NOTICE DG
Keywords: Famille; Femmes; Travail

Domaine des soeurs grises de Montréal - Gauthier, Raymonde (Les chemins de la mémoire. Monuments et sites historiques du Québec, 1991)
Keywords: Femmes; Patrimoine; Soeurs Grises

Prisons, Reformatories, and Convents: The Origin and Nature of Nineteenth Century Female Incarceration Facilities in Montreal - Myers, Tamara (Es Igual Pero Distinto: Essays in the Histories of Canada and Argentina, 1997)
Keywords: Criminalité; Délinquance; Femmes; Prisons

The Homeless, the Whore, the Drunkard, and the Disorderly: Contours of Female Vagrancy in the Montreal Courts, 1810-1842 - Poutanen, Mary Anne (Gendered Pasts: Historical Essays in Femininity and Masculinity in Canada, 1999)
Keywords: Délinquance; Femmes; Itinérance; Prostitution